CHOICE OF TREATMENT IN PATIENTS WITH COMBINED PROSTATE INTRAEPITHELIAL NEOPLASIA OF PERIPHERIC AND CENTRAL ZONES - Melnychuk, M.P. (World of Medicine and Biology, 2023)
The article deals with the problem of prostate intraepithelial neoplasia treatment as a precancerous state. Data of treatment results of 130 patients with prostate intraepithelial neoplasia of peripheric and central zones are analysed. Patients were distributed to groups depending on treatment method: active surveillance, Dutasteride treatment, transurethral prostate resection, and a combination of Dutasteride and transurethral prostate resection. Results were assessed after 3 years of follow-up by detecting of prostate cancer incidence. It was determined that in the active surveillance group prostate cancer rate was 68.8 %. Treatment in patients with prostate intraepithelial neoplasia of peripheric and central zones with Dutasteride decreased prostate cancer rate by 53.8 %, transurethral prostate resection decreased prostate cancer rate by 55.5 % and a combination of Dutasteride and transurethral prostate resection decreased prostate cancer rate by 54.5 %. Obtained data demonstrate the effectiveness of prostate cancer chemoprevention by prostate intraepithelial neoplasia treatment.
Keywords: prostate intraepithelial neoplasia; Dutasteride; transurethral prostate resection